2016
DOI: 10.1007/s40471-016-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cancer Risk and Outcomes Within US Latinos by National Origin and Genetic Ancestry

Abstract: Latinos have lower rates for most common cancer sites and higher rates of some less common cancers (gallbladder, liver, gastric, and cervical) than other ethnic/racial groups. Latinos are a highly heterogeneous population with diverse national origins, unique genetic admixture patterns, and wide spectrum of socio-demographic characteristics. Across the major cancers (breast, colorectal, prostate, lung, and liver) US-born Latinos have higher incidence and worse survival than foreign-born, and those with low-soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 87 publications
2
82
0
2
Order By: Relevance
“…This finding is consistent with previous reports (40,42,60). However, there is a lot of variation within Hispanic subgroups and additional work is needed [57]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous reports (40,42,60). However, there is a lot of variation within Hispanic subgroups and additional work is needed [57]. …”
Section: Discussionmentioning
confidence: 99%
“…42 Both younger age at first birth and higher parity are associated with lower breast cancer risk and are more common in Hispanic women, particularly among those who are foreign-born. 43 For example, breast cancer mortality rates in foreign-born Mexican women living in California were 28% lower than those in their US-born counterparts (12.9 per 100,000 population vs 18.0 per 100,000 population, respectively, during 2008-2012). 29 Similarly, an analysis of Florida vital statistics data indicated that, compared with other Hispanic subgroups, Puerto Rican and Cuban women had the highest breast cancer mortality rates, approaching those of NHW women, consistent with the lower parity in these groups.…”
Section: Female Breastmentioning
confidence: 97%
“…Both incidence and death rates are approximately 30% lower in Hispanics than in NHWs (Table ), largely because of differences in detection practice (incidence only) and reproductive patterns and other hormonal factors that influence breast cancer risk . Both younger age at first birth and higher parity are associated with lower breast cancer risk and are more common in Hispanic women, particularly among those who are foreign‐born . For example, breast cancer mortality rates in foreign‐born Mexican women living in California were 28% lower than those in their US‐born counterparts (12.9 per 100,000 population vs 18.0 per 100,000 population, respectively, during 2008‐2012) .…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women living in Florida state with Puerto-Rican and Cuban background have higher rates of BC than with Mexican and from other Latin American countries' background. It has been reported higher risk of BC among in-born US Latinas, longer time of US residency, residence in higher socioeconomic area and non-Hispanic neighborhood [9]. Latinas living in the USA are associated with shorter survival.…”
mentioning
confidence: 99%